From fabrication to mechanical properties: exploring high-entropy oxide thin films and coatings for high-temperature applications - Lee, Jun Yeop; Cai, Wenjun (Frontiers in Coatings, Dyes and Interface Engineering, 2024)
High-entropy oxides (HEOs) containing five or more cations have garnered significant attention recently due to their vastly tunable compositional space, along with their remarkable physical and mechanical properties, exceptional thermal stability, and phase reversibility at elevated temperatures. These characteristics position HEOs as promising candidates for structural components and coatings in high-temperature applications. While much of the ongoing research on HEOs centers around understanding processing-structure relationships, there remains a dearth of knowledge concerning their mechanical properties, crucial for their prospective high-temperature applications. Whether in bulk form or as coatings, the efficacy of HEOs hinges on robust mechanical properties across a spectrum of temperatures, to ensure structural integrity, fracture resistance, and resilience to thermal stress. This review offers a succinct synthesis of recent advancements in HEO research, spanning from processing techniques to mechanical behaviors under extreme conditions. Emphasis is placed on three key aspects:(1) Investigating the influence of processing parameters on HEO crystal structures. (2) Analyzing the interplay between crystal structure and mechanical properties, elucidating deformation mechanisms.(3) Examining the mechanical behavior of HEOs under extreme temperatures and pressures. Through this review, we aim to illuminate the effective control of HEOs' unique structures and mechanical properties, paving the way for their future applications in extreme environments.